Political Islam: The shrinking trend and the future trajectory of Islamic political parties in Indonesia - Ahmad Khoirul Umam; Akhmad Arif Junaidi (Masyarakat, Kebudayaan dan Politik, 2017)
The trend of religious conservatism in Indonesian public sector is increasing nowadays. But the trend is not followed by the rise of political Islam‟s popularity. The Islamic political parties are precisely abandoned by their sympathizers because of some reasons. This paper tries to elaborate the reasons causing the erosion of Islamic parties‟ political legitimacy. Some fundamental problems such as inability to transform ideology into political platform, internal-factionalism, as well as the crisis of identity will be explained further. The experience from 2009 election can be used to revitalize their power and capacity for the better electability in the next 2014 election. But they seem to be unable to deal with the previous problems making the electability erosion in 2014 more potential and inevitable. Various strategies must be conducted by the parties such as consolidation, revitalizing their political communication strategy, widening political networks across various ideological and religious streams, and others. Without that, their existence would be subordinated by the secular parties to become the second class political players in this biggest Moslem country in the world.